Effects of feeding different proportions of steam-flaked corn-based starter on growth performance, immunity and serum metabolism of pre-weaned Simmental calves - Yao, Kangyu; Gao, Yu; Yang, Liang; Yang, Min; Wu, Xiuyu; Zhang, Xinyu; Lv, Zhengke; Shao, Wei; Wei, Yong; Ren, Wanping (Frontiers in Veterinary Science, 2025)
IntroductionThis study examines the effects of steam-flaked corn starter on pre-weaned Simmental calves' growth, immunity, and metabolism. Despite benefits shown in adult cattle, research on calves is limited. The goal is to optimize calf feeding for better growth, health, and nutrient use.MethodsThirty-two Simmental bull calves (avg. wt: 50.50 ± 4.50 kg, avg. age: 21 ± 7 days) were divided into four groups of eight. The 127-day study included a 7-day pretest and a 120-day trial. Calves had unlimited access to starter feed, alfalfa hay, and water. Groups received starter diets with 0% (CK, control), 33% (SFC33, low), 66% (SFC66, medium), or 100% (SFC100, high) steam-flaked corn replacing regular corn. Other conditions were consistent.ResultsFeeding 33% steam-flaked corn to pre-weaned Simmental calves led to highest daily weight gain (0.80 kg/d), significantly boosting serum globulin, cholesterol, urea nitrogen, glucose, immunoglobulins, GH, INS, and IGF-1 (P < 0.05). Compared to control, 31 metabolites differed in SFC33 group, mostly up-regulated, including glycerophospholipids, linoleic/arachidonic acid metabolism, cholesterol pathway molecules, L-glutamine in multiple pathways, and mannose in fructose/mannose metabolism.DiscussionIn summary, feeding 33% steam-flaked corn-based starter can improve the growth performance, enhance immunity, and improve sugars, lipids, and proteins metabolism of pre-weaned Simmental calves.